Perfluoroalkyl Substance Exposure and the BDNF Pathway in the Placental Trophoblast - Marchese, Melissa J.; Li, Shuman; Liu, Bin; Zhang, Jun J.; Feng, Liping (Frontiers in Endocrinology, 2021)
Background Per- and polyfluoroalkyl substances (PFAS) are persistent organic pollutants that have become globally ubiquitous in humans and the environment. In utero PFAS exposure is associated with neurodevelopmental effects; however, the mechanism is poorly understood. Brain-derived neurotrophic factor (BDNF) signaling is critical to fetal neurodevelopment during pregnancy and maintains important regulatory roles later in life. This study aims to characterize placental BDNF signaling and investigate whether PFAS exposure disrupts the signaling pathway in placental trophoblast cells. Methods The expression and localization of BDNF receptors–p75NTR and TrkB–in first trimester and term human placentas and trophoblast cells were investigated by immunofluorescence staining. To assess the effects of PFAS exposure on the BDNF pathway, BeWo cells were treated with PFAS mixtures that mimicked blood levels in a highly exposed population and major PFAS compounds in the mixture at 0.01, 0.1, 1, and 10 M concentrations. Changes in pro-BDNF levels and phosphorylation of TrkB receptors were examined by Western blot. Results In first trimester human placentas, TrkB and p75NTR receptors were primarily localized to syncytiotrophoblast and cytotrophoblast cells. At term, TrkB and p75NTR receptors were primarily observed in the placental villous stroma. TrkB receptor staining in trophoblasts was reduced at term, while p75NTR receptor staining was negative. TrkB receptors were confined to the nuclear and perinuclear spaces, and phosphorylation occurred at the Tyr816 residue in BeWo cells. Exposure to PFOS, PFOA, PFBS, and the six-PFAS mixture did not significantly affect BDNF levels or activation (phosphorylation) of TrkB. Treating cells with 1 μM and 10 μM of PFNA resulted in increased TrkB phosphorylation compared to unexposed controls, but BDNF levels were unchanged. Conclusions BDNF receptors are present in different regions of human placental villi, indicating diverse functions of BDNF signaling in placental development. Our findings suggest that the BDNF pathway in placental trophoblast cells is not disrupted by exposures to PFOS, PFOA, PFBS, and a PFAS mixture, but may be affected by PFNA exposures. Further investigation is needed on how PFAS affects other critical signaling pathways during fetal neurodevelopment.